The Effect of Socialization on the Implementation of the MBKM Curriculum Policy for Civil Engineering Students at Universitas Komputer Indonesia - Pratiwi, VItta (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The goal of this study was to see how socialization affected the implementation of the